The Relations Between Green Building Concept and Pro-Environmental Behavior in Vertical Housing - Rachmaniatus Syahriyah, Dewi; Aryacitra Bhaskara, Panji (KnE Social Sciences, 2019)
Residential building in a post-occupation phase and building operations consume large amounts of energy and cause environmental degradation. To reduce the negative impact of energy consumption in residential building, green concept through occupant behavior (pro-environment behavior) is useful. Implementation of green concepts on buildings is expected to trigger the emergence of pro-environmental behavior. This study aims to analyze the correlation of green values in a residential building with the value of pro-environmental behavior, especially on student vertical housing. Based on purposive sampling (non-random/non-probability sampling), correlation analysis shows that the concept of green building has a high correlation with a significant value of <0.05 towards pro-environmental behavior. The application of the green concept in improving pro-environmental behavior can be made by considering three priority categories, namely the site development, energy efficiency, and the use of materials. Keywords: green concept, pro-environmental behavior, vertical housing